Sound: a non-invasive measure of cough intensity - Lee, Kai K (BMJ Open Respir Res, 2017)
INTRODUCTION: Cough intensity is an important determinant of cough severity reported by patients. Cough sound analysis has been widely validated for the measurement of cough frequency but few studies have validated its use in the assessment of cough strength. We investigated the relationship between cough sound and physiological measures of cough strength. METHODS: 32 patients with chronic cough and controls underwent contemporaneous measurements of voluntary cough sound, flow and oesophageal pressure. Sound power, peak energy, rise-time, duration, peak-frequency, bandwidth and centroid-frequency were assessed and compared with physiological measures. The relationship between sound and subjective cough strength Visual Analogue Score (VAS), the repeatability of cough sounds and the effect of microphone position were also assessed. RESULTS: Sound power and energy correlated strongly with cough flow (median Spearman’s r=0.87–0.88) and oesophageal pressure (median Spearman’s r=0.89). Sound power and energy correlated strongly with cough strength VAS (median Spearman’s r=0.84–0.86) and were highly repeatable (intraclass correlation coefficient=0.93–0.94) but both were affected by change in microphone position. CONCLUSIONS: Cough sound power and energy correlate strongly with physiological measures and subjective perception of cough strength. Power and energy are highly repeatable measures but the microphone position should be standardised. Our findings support the use of cough sound as an index of cough strength.